Pengaruh Orientasi Kewirausahaan dan Daya Saing terhadap Kinerja Bisnis: (Studi pada UD Sanjaya) - Rinova, Dora; Gunevi, Adetya Putra; Oktaviannur, M. (Prodi Administrasi Bisnis FISIP Universitas Tulang Bawang Lampung, 2024)
In the competitive landscape of the snack industry, every business player is required to possess a strong entrepreneurial orientation to achieve the desired goals. Entrepreneurial orientation in the context of snack sales involves the ability to create new and different things. This includes creative thinking and innovative action to generate new opportunities. Thus, this effort encourages individuals to have enthusiasm, a proactive attitude, adaptive behavior, and the necessary skills to manage a business or activity focused on the exploration, creation, and implementation of new ways of working, technologies, and products. Data collection was carried out directly using questionnaires and interviews with employees at UD Sanjaya. The analysis used to determine the influence of independent variables on dependent variables is quantitative statistical analysis. The results of the study are as follows: Entrepreneurial orientation (X1) partially influences business performance, Competitiveness (X2) partially influences business performance (Y), and Entrepreneurial orientation (X1) and competitiveness (X2) simultaneously influence business performance (Y). Keywords: entrepreneurial orientation, competitiveness, business performance